Aqueous extract of Pinus caribaea inhibits the damage induced by ultraviolet radiations, in plasmid DNA - Marioly Vernhes Tamayo; André Schuch Passaglia; Fabiana Fuentes-León; Carlos F. Martins Menck; Ángel Sánchez-Lamar (Journal of Pharmacy & Pharmacognosy Research, 2017)
Context: The incidence of solar ultraviolet radiation (UV) on Earth has increased due to diminish of the ozone layer. This enviromental agent is highly genotoxic causing numerous damage in DNA molecule. Nowadays there is a growing interest in the search of compounds capable to minimize these effects. In particular, phytocompounds have been tested as excelent candidates for their antigenotoxic properties.